Factors influencing utilization of healthcare services for internal migrant older adults in Xuzhou, China: based on Anderson’s model - Li, Guiyuan; Qi, Zijian; Yu, Wenxin; Wang, Qingzhi; Hou, Hao; Miao, Chunxia; Yan, Wenjun; Gao, Xiuyin (Frontiers in Public Health, 2024)
BackgroundAs population migration increases and the aging process accelerates, the number of migrant older adults is growing significantly. This trend presents a substantial challenge to urban health services in regions experiencing an influx of older adults individuals. Consequently, examining the healthcare service utilization of the migrant older adults population is crucial to promote healthy aging.MethodsA multi-stage random sampling method was employed to select a study population of 568 migrant older adults individuals, aged 60 years and above, residing in urban Xuzhou City. Multivariate logistic regression analysis, based on Anderson’s model, was conducted to explore the factors influencing outpatient and inpatient health service utilization among this population.ResultsAmong the 568 migrants, 73 (12.9%) had received outpatient services within the past 2 weeks, while 109 (19.2%) had received inpatient services within the past year. Migrant older adults with education level, time to health centers, and self-assessed health status negatively influenced the outpatient services utilization among migrant older adults. Possession of pension insurance, convenience to visit, sick for the past 2 weeks, and health services need positively influenced the outpatient services utilization among migrant older adults. Furthermore, age, possession of pension insurance and health insurance, convenience to visit, number of chronic diseases, sick for the past 2 weeks, and healthcare service need positively influenced inpatient service utilization among migrant older adults. Education level, self-assessed health status, and time to health centers negatively influenced the inpatient services utilization among migrant older adults.ConclusionThe overall utilization of healthcare services by migrant older adults in Xuzhou remains inadequate. Addressing this issue requires enhanced medical policy support and assistance, stronger health education initiatives, and improved social integration for the older adults. Additionally, efforts should be made to reduce their financial burdens and improve the accessibility of healthcare services.